Strategies for Improving Local Food Security in Developing Countries - Sari, Ratna; Muslim, Muslim; Ameliana, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to examine strategies for improving local food security in developing countries through a comprehensive literature review. Research Design and Methodology: The research design involves a systematic analysis of academic literature focusing on dimensions of food security, including availability, access, utilization, and stability of food resources. Methodologically, this review synthesizes findings. Findings and Discussion: The findings underscore the multifaceted nature of food security, emphasizing the importance of technological advancements, market-based interventions, social protection programs, community-based initiatives, and policy reforms. Technological advancements such as high-yield crop varieties and precision farming techniques have shown potential in enhancing agricultural productivity and resilience to climate change. Market-based interventions, including improved infrastructure and storage facilities, can reduce transaction costs and stabilize food prices. Social protection programs, such as cash transfers and food assistance, provide immediate relief to vulnerable populations. Community-based initiatives empower local communities to address specific food security challenges. Policy reforms at both national and international levels are essential for creating an enabling environment that supports food security. Implications: The implications of this research highlight the need for coordinated efforts among governments, international organizations, and local communities to address food security challenges holistically. These findings contribute to a nuanced understanding of food security dynamics and offer evidence-based recommendations for policymakers and practitioners.